Emerging souvenirs—clinical presentation of the returning traveller with imported arbovirus infections in Europe. (March 2018) - Eckerle, I.; Briciu, V.T.; Ergönül, Ö.; Lupşe, M.; Papa, A.; Radulescu, A.; Tsiodras, S.; Tsitou, C.; Drosten, C.; Nussenblatt, V.R.; Reusken, C.B.; Sigfrid, L.A.; et al.
Abstract: Background: Arboviruses are an emerging group of viruses that are causing increasing health concerns globally, including in Europe. Clinical presentation usually consists of a nonspecific febrile illness that may be accompanied by rash, arthralgia and arthritis, with or without neurological or haemorrhagic syndromes. The range of differential diagnoses of other infectious and noninfectious aetiologies is broad, presenting a challenge for physicians. While knowledge of the geographical distribution of pathogens and the current epidemiological situation, incubation periods, exposure risk factors and vaccination history can help guide the diagnostic approach, the nonspecific and variable clinical presentation can delay final diagnosis. Aims and sources: This narrative review aims to summarize the main clinical and laboratory-based findings of the three most common imported arboviruses in Europe. Evidence is extracted from published literature and clinical expertise of European arbovirus experts. Content: We present three cases that highlight similarities and differences between some of the most common travel-related arboviruses imported to Europe. These include a patient with chikungunya virus infection presenting in Greece, a case of dengue fever in Turkey and a travel-related case of Zika virus infection in Romania. Implications: Early diagnosis of travel-imported cases is important to reduce the risk of localized outbreaks of tropical arboviruses such as dengue and chikungunya and the risk of local transmission from body fluids or vertical transmission. Given the global relevance of arboviruses and the continuous risk of (re)emerging arbovirus events, clinicians should be aware of the clinical syndromes of arbovirus fevers and the potential pitfalls in diagnosis.